Pengaruh Inflasi, Kurs (dollar/rupiah), Suku bunga SBI terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia - Zein Hudha Firmansyah; Sishadiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to inform about the influence of inflation, exchange rate (dollar/rupiah), bi interest rates on the composite stock price index. The data sample taken in this research is a type of secondary time series data with a time range from 2007-2022 sourced from BPS, Yahoo Finance, BI, BEI. The data analysis used used multiple linear regression analysis with the Ordinary Least Square (OLS) model via SPSS 25. The results of the study concluded that the inflation variable had no significant and positive effect on the IHSG, the exchange rate variable (dollar/rupiah) had a significant and positive effect on the IHSG, The BI interest rate variable has a significant negative influence on the IHSG.